Urokinase-Treated Antithrombogenic Drains and Optimized Drain Placement in Endoscopic Lumbar Decompressive Surgery - Nakamura, Shu; Ikeda, Shoji; Taguchi, Mitsuto (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2016)
Background Spinal epidural hematoma (SEH) frequently occurs after microendoscopic decompressive laminotomy (MEDL), and a drain may not be functioning sufficiently.Objective To reduce the incidence of SEH after MEDL.Methods  A urokinase-treated antithrombogenic drain, which is available only with a large diameter, was reduced in diameter and used after MEDL. Magnetic resonance imaging (MRI) and computed tomography (CT) were performed 36 to 48 hours after surgery. The size of the SEH was measured by MRI, and the location of the drain tip was assessed by CT scan. After imaging, the drain was removed.Results Use of the urokinase-treated antithrombogenic drain reduced the incidence of SEH. However, the drain was not adequately placed in many cases, limiting the effect of the drainage. When the urokinase-treated antithrombogenic drain was placed contralaterally to the approach side using an unsheathed endoscope, the incidence of SEH was further reduced.Conclusions The urokinase-treated antithrombogenic drain prevented thrombus-related drain obstruction. In addition, unsheathed endoscopic contralateral placement of the drain was effective for SEH prevention.
Keywords: drain; endoscopic laminotomy; hematoma